1996
DOI: 10.1203/00006450-199608000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Serum Cortisol, Dehydroepiandrosterone Sulfate, and Steroid-Binding Globulins in Preterm Neonates: Effect of Gestational Age and Dexamethasone Therapy

Abstract: Our aim was to assess adrenocortical function in very low birth weight infants, specifically to evaluate the impact of gestational age and dexamethasone (DEX) therapy on serum concentrations of total and free cortisol, dehydroepiandrosterone sulfate (DHEAS), and steroid-binding globulins. Twelve moderately preterm or full-term neonates of 38 +/- 4 (mean +/- SD) wk of gestation and 36 ill preterm neonates of 26 +/- 2 (mean +/- SD) wk of gestation were studied. Twenty-three of the 36 ill preterm neonates partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
41
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(47 citation statements)
references
References 33 publications
6
41
0
Order By: Relevance
“…By doing so, we observed a significant difference in blood-spot 17-OHP concentration among groups, whereas other potentially influential variables (gestational age, infectious disease, RDS, and so on) were similar. Several studies of the impact of antenatal corticosteroids on adrenal function, totaling Ͼ200 premature infants, have shown that antenatal therapy decreases blood cortisol and dehydroepiandrosterone sulfate by~50% for 7 d after birth (25,26). Overall, these results suggest that our observation of an impact of antenatal corticosteroid on blood 17-OHP should not be surprising, although this impact was dependent on the cumulative dose and/or the number of courses of betamethasone.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…By doing so, we observed a significant difference in blood-spot 17-OHP concentration among groups, whereas other potentially influential variables (gestational age, infectious disease, RDS, and so on) were similar. Several studies of the impact of antenatal corticosteroids on adrenal function, totaling Ͼ200 premature infants, have shown that antenatal therapy decreases blood cortisol and dehydroepiandrosterone sulfate by~50% for 7 d after birth (25,26). Overall, these results suggest that our observation of an impact of antenatal corticosteroid on blood 17-OHP should not be surprising, although this impact was dependent on the cumulative dose and/or the number of courses of betamethasone.…”
Section: Discussionsupporting
confidence: 52%
“…In view of our results, a moderate level of blood-spot 17-OHP in a premature infant who has received multiple courses of antenatal steroids should be the object of careful interpretation. Because antenatal glucocorticoids may suppress adrenal function for~1 wk after birth (25,26), a second screening test for CAH at 1-2 wk of age could be recommended for these infants. Initially proposed to detect more cases of simple virilizing CAH in term newborns (35), this would be useful for premature infants, provided that salt loss is monitored carefully between the two screenings.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, infants born at lower gestational ages who are sickest commonly show low basal cortisol and adrenal insufficiency (e.g. Hanna et al, 1997;Kari et al, 1996;Ng et al, 2001;Scott and Watterberg, 1995). In addition, preterm infants recovering from chronic lung disease may show decreased cortisol in response to ACTH 3 weeks after birth (Watterberg et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Several authors reported basal cortisol levels in neonates to be depressed within 6 hours of treatment with dexamethasone or betamethasone and to remain low for 7 days. 26,27 Some studies indicate that extremely preterm and severely ill infants have surprisingly low basal cortisol. The reasons for this have been suggested to be reduced ability to respond adequately to stress, because of either an inability to produce cortisol or an inability to recognize the stress and/or an inappropriate corticotropin-releasing hormone release.…”
mentioning
confidence: 99%